The Calm Corner Approach as an Inclusive Counseling and Psychotherapy Service in Early Childhood Education: A Case Study Indonesia - Warlan Sukandar; Mohd Khairul Anuar Rahimi; Nur Rahmi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to analyze the implementation of the Calm Corner approach as a developmental counseling and psychotherapy service in inclusive early childhood education at TK Islam Insan Mandiri Nabire. The study employed a descriptive qualitative approach with a case study design involving two inclusive children, one classroom teacher, and one teaching assistant. Data were collected through observation, in-depth interviews, and documentation, while children's developmental progress was assessed using a 1–4 rating scale. Data analysis was conducted using the Miles and Huberman interactive model and was supported by quantitative analysis of the children's developmental scores. The findings indicate that the Calm Corner functions as a safe and supportive environment that helps children regulate their emotions, enhance self-awareness, and develop independent self-soothing abilities. Quantitative analysis revealed significant improvements in socio-emotional development. The average emotional score increased from 1.5 to 3.0, with a gain of 1.5 (high category), while the average social score increased from 1.5 to 3.0, with a gain of 1.5 (high category). In terms of behavioral development, the average score increased from 2.0 to 3.0, a gain of 1.0 (moderate category), as reflected in reduced aggressive behaviors and improved adaptive learning behaviors. The consistency of observations between the two observers demonstrated strong data validity. Therefore, the Calm Corner approach is effective as a developmental counseling and psychotherapy service in supporting the social, emotional, and behavioral development of inclusive early childhood learners. Keywords: calm corner, inclusive child counseling, developmental psychotherapy, early childhood education, emotional regulation